Distribution pattern of diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae) on choy-sum plants - Tock, Hing Chua; BH Lim (Blackwell Publishing Ltd, 1979)
The distribution of all life-stages of Plutella xylostella (L.) on Choy-sum plants (Brassica rapa var. Spinach mustard) was investigated. The adults had a random distribution (P > 0.05), while the immature stages had a negative binomial (aggregated) distribution (P > 0.05). The adults and eggs were found mainly on the upper surface (P < 0.001) while the larvae (except the first instar) and pupae on the lower leaf surface (P < 0.001). The first instars were usually in the mines of leaves hollowed out by their feeding activities. The adults (P < 0.05), eggs (P < 0.001) and larvae (P < 0.05) were recorded mainly on the fully-opened leaves of intermediate age while the pupae (P < 0.01) on the oldest (also lowest) leaves. The larvae after hatching from eggs tended to clump together although they later dispersed as they grow, only to aggregate again during pupation.